Metal and flesh : the evolution of man : technology takes over - Dyens, Ollivier (Leonardo (Series) (Cambridge, Mass.), 2001)
"For more than 3,000 years, humans have explored uncharted geographic and spiritual realms. Present-day explorers face new territories born from the coupling of living tissue and metal, strange lifeforms that are intelligent but unconscious, neither completely alive nor dead. Our bodies are now made of machines, images, and information. We are becoming cultural bodies in a world inhabited by cyborgs, clones, genetically modified animals, and innumerable species of human/information symbionts. Ollivier Dyens's Metal and Flesh is about two closely related phenomena: the technologically induced transformation of our perceptions of the world and the emergence of a cultural biology. Culture, according to Dyens, is taking control of the biosphere. Focusing on the twentieth century--which will be remembered as the century in which the living body was blurred, molded, and transformed by technology and culture--Dyens ruminates on the undeniable and irreversible human/machine entanglement that is changing the very nature of our lives"--Provider website